PENYELESAIAN SENGKETA BATAS WILAYAH DESA DINAS STUDI KASUS SENGKETA BATAS WILAYAH ANTARA DESA DINAS TULIKUP DENGAN DESA DINAS SIDAN DI KABUPATEN GIANYAR - Utomo, Yuli (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 1 (2015)DO - 10.24843/JMHU.2015.v04.i01.p12, 2015)
Village Boundary Dispute Resolution service is the application of dispute resolution regulations village boundaries under applicable rules applied to public office in the village of Gianyar regency. This study aims to examine government policies and values ??- the value of local knowledge related to conflict resolution Dispute resolution limit of the village of Dinas in Gianyar regency. The results showed that completion of the boundary dispute in the village of Gianyar Regency Office is dominated by non-litigation settlement patterns, deliberation, and mediation. Thus, the principles of law, social change and the rule of law in conflict resolution need to be nurtured, preserved, and disseminated to the general public.
Keywords: Village Boundaries Dispute Resolution, Government Resolutions regulations